Pendampingan Aplikasi Catatan Keuangan Sebagai Pembukuan Usaha Digital UMKM Desa Mranggonlawang - Alifia Iga Sutrisno; Risqi Firdaus Setiawan; Taufikurrahman Taufikurrahman (jurnal ABDIMAS Indonesia, 2023)
Many of the MSMEs are only focused on their sales and marketing strategies and then ignore their company's financial reports. Business financial reports are important for every business because they can provide an overview of the company's performance and the current state of the business. The problem of managing funds is a key factor that can lead to the success or even failure of MSMEs. ). Errors in cash management can make MSMEs suddenly no longer have cash for operational needs every day. In this assistance, the author introduces an application that can be applied via a smartphone called Financial Records. The purpose of this mentoring activity is to equip MSMEs with the knowledge and skills to make digital financial reports. In addition, it is hoped that in the long term it will change the behavior and culture of oral in business to become written. The method used is action research in which the author makes observations about which MSMEs need assistance regarding their financial management. In this activity get a positive response from both partners. Authors together with partners share information and practice preparing financial reports together. Through this activity, Cemal – cemil By Dian and Finza Cake & Cookies partners already have the Financial Records application and are proficient in managing it